Pavilion of the Lusatian Culture Archaeological Reserve in Częstochowa-Raków – a Case Study - Malec-Zięba, Emilia (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2024)
This article presents the history, unique architecture and current status of the Archaeological Reserve in Częstochowa-Raków. Located at the site of the discovery of one of the largest cemeteries of the Lusatian culture (750-600 BC), the reserve was opened in 1965 as the first in situ museum in Poland. The author of the original design of the exhibition pavilion was Włodzimierz Ściegienny, who approached his task in a unique and multifaceted way. The pavilion stood out for its innovative structural solutions, unique mosaics and space arrangement. Despite its historical and artistic value, the building was remodelled in 2001, resulting in the loss of its original form. The article documents the lost project of Ściegienny, highlighting its significance for Polish culture and the history of the 20th century.